Ewing Sarkoma: Ulasan Singkat Keganasan: Indonesia - Rafi Gutra Aslam; Helmi Ismunandar; Risal Wintoko; Exsa Hadibrata; Anisa Nuraisa Jausal (Medula, 2023)
A malignancy that identified first by James Ewing in 1921. Ewing sarcoma is a malignancy of the bones caused by abnormal activity of progenitor cell mesenchymal occurs by a genetic factor where the patient had a combination of translocation chromosome non-random in t(11; 22) (q24;q12) or t(21; 22) (q22; q12). The patient will have pathognomonic findings of periosteal reaction similar to "Onion skin", lesions like “Moth-eaten”, and “Codman’s Triangle” in radiology findings. Second highest malignancy bone prevalent worldwide after osteosarcoma. This malignancy occurs commonly in the male gender, incidence peaked in the approximately first decade in life with a prognosis range of about 5 years more or less. The malignancy occurs in the metaphysis-diaphysis part of the bone that has a variety of prognoses based on stage, metastasis, and therapy. Literature Review method is used in this article writing by article, journal, and book that review shortly about Ewing sarcoma from multi-aspect of etiology, epidemiology, pathogenesis and pathophysiology, clinical manifestations, treatment, staging, prognosis, complication, and education as the last topic. Prognosis of Ewing Sarcoma patient will be better if given multimodal therapy including chemotherapy, radiotherapy, and operation that adjusted with the condition in every patient. Nevertheless, further research is needed about best treatment in goals to extend patient survivability and enhance prognoses approximately in 3 years.